Impact of quality management practices on quality performance and financial performance: evidence from Indian manufacturing companies. (3rd May 2016) - Parvadavardini, S.; Vivek, N.; Devadasan, S.R.
Abstract : The 'quality performance–financial performance' relationship has been significantly studied in managerial literature. However, no definite quantification has been given regarding its type. This study aims to explore the relationship between quality management (QM) practices, quality performance and financial performance of the manufacturing firm. First, critical QM practices have been identified and classified into categories. Then, a structural model linking these practices, quality performance and financial performance factors has been proposed and empirically tested. The empirical data were obtained from a questionnaire-based survey of 152 Indian manufacturing companies. After the data were collected, the scales were purified using loading values and composite reliability. The resultant purified scales were then tested for convergent validity through partial least-square path modelling using Visual PLS software. The result showed a positive relationship between QM practices, quality performance and financial performance. In addition, the result illustrates the direct impact of quality performance on financial performance.